Functional characterisation of naturally occurring mutations in human melanopsin - Rodgers, J; Peirson, SN; Hughes, S; Hankins, MW (Springer, 2018)
Melanopsin is a blue light-sensitive opsin photopigment involved in a range of non-image forming behaviours, including circadian photoentrainment and the pupil light response. Many naturally occurring genetic variants exist within the human melanopsin gene (OPN4), yet it remains unclear how these variants affect melanopsin protein function and downstream physiological responses to light. Here, we have used bioinformatic analysis and in vitro expression systems to determine the functional phenotypes of missense human OPN4 variants. From 1242 human OPN4 variants collated in the NCBI Short Genetic Variation database (dbSNP), we identified 96 that lead to non-synonymous amino acid substitutions. These 96 missense mutations were screened using sequence alignment and comparative approaches to select 16 potentially deleterious variants for functional characterisation using calcium imaging of melanopsin-driven light responses in HEK293T cells. We identify several previously uncharacterised OPN4 mutations with altered functional properties, including attenuated or abolished light responses, as well as variants demonstrating abnormal response kinetics. These data provide valuable insight into the structure–function relationships of human melanopsin, including several key functional residues of the melanopsin protein. The identification of melanopsin variants with significantly altered function may serve to detect individuals with disrupted melanopsin-based light perception, and potentially highlight those at increased risk of sleep disturbance, circadian dysfunction, and visual abnormalities.